2009
DOI: 10.1111/j.1440-1835.2009.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Research note: Identity of the Qingdao algal bloom

Abstract: In early July 2008, news agencies worldwide reported on a vast algal bloom that was threatening the upcoming Olympic sailing events in Qingdao, China. The identity of the culpable alga, however, remained undiscussed. We have identified the alga that caused the bloom by means of morphological and molecular data, including sequence data of the plastid encoded large subunit ribulose 1,5-bisphosphate carboxylase gene (rbcL) and the nuclear encoded rDNA internal transcribed spacer (ITS) region. The bloom-forming al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(101 citation statements)
references
References 25 publications
6
93
0
2
Order By: Relevance
“…Leliaert et al (2009) concluded that the species from 2008 Qingdao was part of the Ulva linza-proceraprolifera (LPP) complex, whereas Wang et al (2010) concluded that the alga was U. prolifera. Zhang et al (2011) reported that the blooming species forming the floating mats in the YS in 2008 and 2009 was U. prolifera based on a 5S rDNA spacer sequence analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Leliaert et al (2009) concluded that the species from 2008 Qingdao was part of the Ulva linza-proceraprolifera (LPP) complex, whereas Wang et al (2010) concluded that the alga was U. prolifera. Zhang et al (2011) reported that the blooming species forming the floating mats in the YS in 2008 and 2009 was U. prolifera based on a 5S rDNA spacer sequence analysis.…”
Section: Methodsmentioning
confidence: 99%
“…While so- The fifth putative cause of the blooms has been a general attribution to eutrophication (e.g., Leliaert et al, 2009) or enhanced nutrient supply from increased rainfall . Enteromorpha (Ulva) species have been shown to have a high nitrogen requirement for optimal growth (Poole and Raven, 1997).…”
Section: Origin and Possible Cause Of Bloomsmentioning
confidence: 99%
“…Since that time, various news reports and scientific articles have described the event, discussed the causes, evaluated the consequences and studied the biology of U. prolifera. Fu et al (2008), , Leliaert et al (2009), Li et al (2009), Liu et al (2010a,b) and Pang et al (2010) studied aspects of its biology and genetics. The scale of the bloom and its movement was described using satellite tracking methods by Hu and He (2008), Hu (2009), , Shi and Wang (2009) and Hu et al (2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The green seaweeds (Ulvophyceae) abound in coastal habitats. Some green seaweeds (mainly Ulva) can form extensive, free-floating coastal blooms, called 'green tides' (Leliaert et al, 2009c); others, like Caulerpa and Codium are notorious for their invasive nature (Meinesz & Hesse, 1991;Jousson et al, 2000;Lapointe et al, 2005). The prasinophytes are planktonic green algae that occur mainly in oceanic environments and are especially abundant in more eutrophic, near-shore waters, where they can form monospecific blooms (O'Kelly et al, 2003;.…”
mentioning
confidence: 99%